STUDI LITERATUR: ANALISIS KEBERHASILAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS LECTORA INSPIRE PADA PESERTA DIDIK - Mitha, Mitha; Wahyuni, Eko Sri; Afandi, Afandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
The incorporation of digital media in education is increasingly recognized as essential for facilitating interactive and effective learning experiences. This study conducts a systematic review of eight national journal articles that focus on the development and application of Lectora Inspire as an educational tool across multiple subjects. Employing a literature review approach, the research examines publications from 2016 to 2024 by analyzing the methodologies, instruments, findings, and conclusions presented in each article. The findings indicate that Lectora Inspire-based media consistently achieve high validity ratings from experts and receive positive feedback from both educators and students. Evidence from the reviewed studies demonstrates that this media enhances student learning outcomes, reflected in improved posttest results and heightened learner engagement throughout the instructional process. Its user-friendly nature and adaptability make it well-suited to support personalized learning needs. Consequently, Lectora Inspire is regarded as a valid and effective digital learning medium suitable for diverse educational settings.